2021
DOI: 10.1177/23337214211005223
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 Pandemic and Rate of Cognitive Decline in Patients with Dementia and Mild Cognitive Impairment: A Cross-sectional Study

Abstract: Introduction: Since the declaration of coronavirus disease 2019 (COVID-19) as a pandemic, patients with dementia, were specifically vulnerable to the negative impact of the outbreak. Objective: To examine the association between lockdown amid COVID-19 pandemic and the rate of cognitive decline among patients with dementia and mild cognitive impairment (MCI). Methods: We conducted a cross-sectional observational study on patients with dementia and MCI who attended the outpatient clinic at Ibn Sina Hospital, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 26 publications
5
42
2
6
Order By: Relevance
“…Responses of people with dementia in our study were consistent with early reports indicating that people with dementia themselves were concerned about increased decline in abilities during lockdown [11,13,14]. While some decline would be expected over time, perceptions of accelerated cognitive decline are supported by studies of memory clinic samples that identi ed steeper trajectories of decline in MMSE scores during the pandemic [50,51]. Perceived decline in cognitive and functional abilities over and above what would normally be expected could be attributable to the effects of pandemic-related restrictive measures, including more social isolation, reduction in usual activities and loss of routine as well as increased carer stress [51].…”
Section: Discussionsupporting
confidence: 88%
“…Responses of people with dementia in our study were consistent with early reports indicating that people with dementia themselves were concerned about increased decline in abilities during lockdown [11,13,14]. While some decline would be expected over time, perceptions of accelerated cognitive decline are supported by studies of memory clinic samples that identi ed steeper trajectories of decline in MMSE scores during the pandemic [50,51]. Perceived decline in cognitive and functional abilities over and above what would normally be expected could be attributable to the effects of pandemic-related restrictive measures, including more social isolation, reduction in usual activities and loss of routine as well as increased carer stress [51].…”
Section: Discussionsupporting
confidence: 88%
“…Responses of people with dementia in our study were consistent with early reports indicating that people with dementia themselves were concerned about increased decline in abilities during lockdown [11,13,14]. While some decline would be expected over time, perceptions of accelerated cognitive decline are supported by studies of memory clinic samples that identified steeper trajectories of decline in MMSE scores during the pandemic [50,51]. Perceived decline in cognitive and functional abilities over and above what would normally be expected could be attributable to the effects of pandemic-related restrictive measures, including more social isolation, reduction in usual activities and loss of routine as well as increased carer stress [51].…”
Section: Discussionsupporting
confidence: 88%
“…It was observed that the most affected cognitive area was memory. As a result, in this study, it was concluded that cognitive functions decreased more rapidly during quarantine in patients with dementia and MCI compared to the pre-pandemic period [ 8 ]. In another study published in 2021, caregivers of MCI and dementia patients were evaluated with a questionnaire.…”
Section: Discussionmentioning
confidence: 99%